Measuring the Service Quality at Multimodal Public Transport Interchanges: A Needs-Driven Approach. Issue 10 (October 2022) - Moodley, Sumashni; Venter, Christoffel
Multimodal interchanges are key components of integrated public transport systems. A better understanding of the perceptions, needs, and priorities of public transport users as they travel through transport interchanges is needed to provide insight into the design of future integrated interchanges that will ultimately benefit users. This paper aims to help fill this gap by describing the development of a tool that can be used to measure the service quality of multimodal interchanges from a passenger's viewpoint, taking into account a set of predefined criteria that can easily and cost effectively be measured on site. A mixed methods approach is discussed, and demonstrated for a case study at three public transport facilities in Durban, South Africa. The results show that users of different genders and age groups have different requirements of interchange facilities, and that knowledge of local preferences is important for effective management and design. The external validity of the multimodal service quality index is demonstrated as it ranks the three facilities in the same order of quality as independent satisfaction ratings obtained from users.